PENGARUH INTENSISTAS PENGGUNAAN APLIKASI TIKTOK TERHADAP INTERAKSI SOSIAL DENGAN KESEJAHTERAAN DIGITAL SEBAGAI VARIABEL MEDIASI DI ERA TEKNOLOGI 5.0 MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2022-2023 - Imelia Imelia; Muazza Muazza; Destri Yaldi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the influence of TikTok usage intensity on students' social interaction, with digital well-being serving as a mediating variable, among Economic Education students (classes of 2022–2023) at the University of Jambi within the context of the Technology 5.0 era. A quantitative approach utilizing a survey method was employed. The sample consisted of 141 students selected via proportionate stratified random sampling. Data were collected using a five-point Likert scale questionnaire. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software to examine the direct and indirect effects between the research variables.The results indicate that TikTok usage intensity has a positive and significant effect on social interaction (t = 3.728; p = 0.000) and on digital well-being (t = 9.362; p = 0.000). Digital well-being also exerts a positive and significant influence on social interaction (t = 6.867; p = 0.000). Furthermore, digital well-being was found to partially mediate the effect of TikTok usage intensity on social interaction (t = 5.440; p = 0.000).The novelty of this study lies in the integration of digital well-being as a mediating variable that explains the mechanism underlying the relationship between TikTok usage intensity and students' social interaction. This study also offers an empirical contribution regarding student digital behavior in the Technology 5.0 era, assessing not only the direct impact of social media but also the digital psychosocial mechanisms influencing social interaction.